Beware of the wolves - Farshtey, Greg.; Ameet Studio (Firm) (New York : Scholastic, 2013)
"The sneaky Wolves have teamed up with the Crocs in the battle for control of all the CHI in Chima! The Lions have only one hope for defeating their enemies: their trusted allies, the Eagles. But are the Eagles clever enough to outwit the scheming Wolves?"--P. [4] of cover.
Battle for CHI -- The hollow tree -- Lone wolf -- Worriz's challenge.
"The Hollow Tree, Lone Wolf, and Worriz's Challenge written by Greg Farshtey."--T.p. verso.
740
Keywords: Crocodiles -- Juvenile fiction; Eagles -- Juvenile fiction; LEGO toys -- Juvenile fiction; Lion -- Juvenile fiction; Wolves -- Juvenile fiction